Development of a method for assessment of dysarthria in a foreign language: a pilot study. (2nd January 2020) - Näsström, Ann-Kristin; Schalling, Ellika
Abstract: Purpose: It is increasingly more common for Speech and Language Pathologists in Sweden to encounter individuals with dysarthria who speak a different language. The aim of the present pilot study was to develop and test a systematic method to be used in collaboration with an interpreter, for assessment of acquired dysarthria in people speaking a language not familiar to the Speech and Language Pathologist. Methods: Seven participants, speaking standard Arabic, were assessed by a Swedish speaking Speech and Language Pathologist using this method and with help of a certified interpreter. The participants were also assessed with equivalent test items from the Swedish "Dysarthria assessment, " with instructions translated to Arabic, by a Speech and Language Pathologist speaking standard Arabic and the results were compared. Results: There were no significant differences between the assessments by the Swedish speaking Speech and Language Pathologist and the Arabic speaking Speech and Language Pathologist in the domains "Respiration and phonation, " "Articulation, " "Listener Comprehension" and "Severity of dysarthria." There was a significant difference between assessments in the domain "Oromotor and velopharyngeal function." Intra- and inter-rater reliability was also calculated using Intraclass Correlation Coefficient and their 95% Confidence Interval. Intra-rater reliability was excellent and inter-rater reliability was very good. Conclusion: The study indicates that a Speech and Language Pathologist, with help of an interpreter, can carry out an assessment of dysarthria in a language unknown to the Speech and Language Pathologist with results comparable to results from an assessment carried out by a Speech and Language Pathologist who speaks the foreign language.